Touch Lib©: humanising a library attendance system in a postgraduate academic institution / Hasniza Amno ... [et al.] - Amno, Hasniza; Kasim, Mohd Jamil; Hashim, Siti Fatimah; Salis @ Saleh, Md Naim; Shaharuddin, Bakiah (Universiti Teknologi MARA, Kedah, 2019)
Touch Lib© is an innovative library attendance system, which is developed using a VB6 programming language and PHP to gather records and monitor library users at Advanced Medical and Dental Institute (AMDI), Universiti Sains Malaysia, Kepala Batas, Pulau Pinang. AMDI is an advanced academic institute recognised for postgraduate programmes, high impact research and tertiary healthcare services. We propose a unique in-house library attendance system which has been designed to fit AMDI’s key functions. This system is advantageous due to its simplicity and cost-effectiveness. Data analysis from the system was transformed into useful knowledge that benefit the library management, delivery of services and future planning of library extension resources for enhanced services. Since its inception in May 2018, the system has empowered AMDI library to escalate its services in line with the vision and mission of the institute and the university. Touch Lib copyright registration number is LY201 8005 416.